Exercise-induced bronchoconstriction: The effects of montelukast, a leukotriene receptor antagonist - James P Kemp (Dove Medical Press, 2009)
James P KempClinical Professor of Pediatrics, Division of Immunology and Allergy, University of California School of Medicine, San Diego, CA, USAAbstract: Exercise-induced bronchoconstriction (EIB) is very common in both patients with asthma and those who are otherwise thought to be normal. The intensity of exercise as well as the type of exercise is important in producing symptoms. This may make some types of exercise such as swimming more suitable and extended running more difficult for patients with this condition. A better understanding of EIB will allow the physician to direct the patient towards a type of exercise and medications that can result in a more active lifestyle without the same concern for resulting symptoms. This is especially important for schoolchildren who are usually enrolled in physical education classes and elite athletes who may desire to participate in competitive sports. Fortunately several medications (short- and long-acting β2-agonists, cromolyn, nedocromil, inhaled corticosteroids, and more recently leukotriene modifiers) have been shown to be effective in preventing or attenuating the effects of exercise in many patients. In addition, inhaled β2-agonists have been shown to quickly reverse the airway obstruction that develops in patients and continue to be the reliever medications of choice. Inhaled corticosteroids are increasingly being recommended as regular therapy now that the role of inflammation and airway injury has been identified in EIB. With the discovery that there is a release of mediators such as histamine and leukotrienes from cells in the airway following exercise with resulting airway obstruction in susceptible individuals, interest has turned to attenuating their effects with mediator antagonists especially those that block the effects of leukotrienes. Studies with an oral leukotriene antagonist, montelukast, have shown beneficial effects in adults and children aged as young as 6 years with EIB. These effects can be demonstrated as soon as two hours and as long as 24 hours after administration without a demonstrated loss of a protective effect after months of treatment. The studies leading up to and resulting in an approval of montelukast for EIB for patients aged 15 years and older are reviewed in this paper.Keywords: asthma, exercise, bronchoconstriction, bronchospasm, leukotrienes, montelukast